CASE STUDY: MANAGEMENT OF VENTRAL HERNIA IN A 2-YEAR-OLD MIXED BREED FEMALE CAT WITH LAPAROTOMY - Gusti Putu Arni Safitri; I Gusti Agung Gde Putra Pemayun; I Wayan Wirata (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Ventral hernia is an abnormality in the median abdomen in the form of a lump caused by incomplete closure of the abdominal wall so that the visceral organs or omentum come out of the abdominal cavity. This case study aims to determine how to diagnose and treat cases of ventral hernia in female cats. A 2-year-old female tortie mix cat weighing 3.58 kg with clinical signs of a lump in the ventral abdomen after an ovariohysterectomy. Supporting examinations were carried out in the form of radiography (x-ray) to support the diagnosis and the results showed a radiolucent image in the area of ​​the lump containing fatty tissue (omentum). The cat was diagnosed with ventral hernia with a fausta prognosis. Treatment was carried out by laparotomy surgery to reposition the contents of the hernia into the abdominal cavity with general anesthesia using a combination of xylazine and ketamine. The closure of the abdominal wall and peritoneum was sutured with a simple interrupted pattern and the subcutaneous part with a simple continuous pattern and combined with subcuticular pattern sutures using Polyglycolic acid 3-0 thread. Postoperatively, the cat was given antibiotiks cefotaxime sodium (20 mg/kg BW, IV, q12h) for 3 consecutive days and continued with Cefixime (10 mg/kg BW, PO, q12h) for 5 consecutive days. On the 11th day, the cat was declared cured with the surgical wound that had healed and dried perfectly with normal appetite and drinking, smooth defecation and urination. It is recommended for owners not to take this condition lightly and a veterinary examination is required to prevent complications that could endanger the animal's health.